2012
DOI: 10.2141/jpsa.0120007
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of Native Chicken from Bangladesh and Neighboring Asian Countries Based on Complete Sequence of Mitochondrial DNA D-loop Region

Abstract: The complete mitochondrial D-loop region was sequenced for a total of 18 individuals of Bangladeshi native chickens (BNC); full feathered (nana) (n=7), naked neck (Nana) (n=8) and Red junglefowl (RJF) (n=3). The alignment of mitochondrial D-loop sequence of these chicken populations with 39 reference sequences from DNA databank; White Leghorn, G. g. murghi, G. g. bankiva, G. g. spadiceus, G. g. gallus and other Asiatic chickens was done to identify the phylogenetic position of BNC for the conservation and impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Nucleotide sequence variation showed 9 haplotypes in CamRJFs, 6 haplotypes in MyaRJFs, 3 haplotypes in BanRJFs and 5 haplotypes in LaoNCs which was corroborated with Nishibori et al (2002) and Islam and Nishibori (2012). Nishibori et al (2002) reported that LaoNCs had low genetic variability based on mtDNA D-loop sequences.…”
Section: Mtdna D-loop Sequence Variation Of Camrjfs Myarjfs Banrjfssupporting
confidence: 67%
See 3 more Smart Citations
“…Nucleotide sequence variation showed 9 haplotypes in CamRJFs, 6 haplotypes in MyaRJFs, 3 haplotypes in BanRJFs and 5 haplotypes in LaoNCs which was corroborated with Nishibori et al (2002) and Islam and Nishibori (2012). Nishibori et al (2002) reported that LaoNCs had low genetic variability based on mtDNA D-loop sequences.…”
Section: Mtdna D-loop Sequence Variation Of Camrjfs Myarjfs Banrjfssupporting
confidence: 67%
“…The other BanRJF2 was grouped with CamRJFs in Clade G. These results suggested that two types of RJF populations exist in Bangladesh, one is an unique in Bangladesh and the other is originated from neighbor countries. Islam and Nishibori (2012) reported that some individuals of Bangladesh chicken populations have a relationship with Japanese native and silky chickens, and also with South East Asian populations of China, Cambodia, Laos, Vietnam, Thailand and Indonesia. Srisulandari et al (2008) reported the five distinct clades within Indonesian native chickens.…”
Section: Banrjfsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kanginakudru et al (2008) found the evidence for domestication of Indian chickens, which were originated from Gallus gallus spadiceus, Gallus gallus gallus and Gallus gallus murghi. Islam and Nishibori (2012) also reported that native fowls in Bangladesh were strongly influenced from Gallus gallus murughi. The domestication of chickens was occurred in Southeast Asia, South China and Indian subcontinent (Liu et al, 2006;Oka et al, 2007).…”
Section: Introductionmentioning
confidence: 96%